“Brick‐Mortar‐Binder” Design toward Highly Elastic, Hydrophobic, and Flame‐Retardant Thermal Insulator - Shanying Sui; Huafeng Quan; Jingxing Wang; Yufang Lu; Yufan Yang; Yuhan Sheng; Zhifang Sun; Yi Zhang (Advanced Science)
Abstract Advanced aerogels hold immense potential in thermal insulation. However, achieving high environmental adaptability aerogel insulators with elasticity, hydrophobicity, flame‐retardancy, and low temperature tolerance remains a significant challenge. Inspired by a “brick‐mortar‐binder” biomimetic texture, a layered double hydroxide/carboxylated cellulose nanofibers/Si–O–Si (LCS) hybrid aerogel is developed by bottom‐up freeze‐drying. Owing to the distinct building blocks and organized structure, as‐prepared LCS hybrid aerogel exhibits impressive mechanical elasticity, cycling stability at an extremely low temperature (‐196 °C), hydrophobicity, and flame‐retardancy (LOI = 44.6%, UL‐94: V‐0). Additionally, the incorporation of layered double hydroxide effectively improves the thermal insulation property (thermal conductivity = 0.0296 W·m−1·K−1). These distinctive features make the LCS hybrid aerogel highly promising for thermal management applications in extreme conditions, such as in pipelines for transporting liquid nitrogen and liquefied natural gas.